Vpliv funkcionalizacij in struktur metakrilatnih monolitov na pretočnosti in kapacitete za različno velike molekule - Smrekar, Vida (visokošolska dela, 2009)
In recent decades much work has been done on the development and optimisation of chromatographic supports in order to achieve efficient purification of biomolecules. Convection Interaction Media (CIM) methacrylate ion-exchange monolithic chromatographic supports are becoming the material of choice for fast separations and purifications of large biomolecules such as large proteins, DNA, viruses, bacteriophages, etc. Due to the specific open-porous structure of monoliths that allows rapid exchange of molecules between the mobile and stationary phase based on the convective transport, the flow independent separation and dynamic binding capacity is exhibited. Pore size of the monolithic media plays an important role in the separation of differentsized molecules. Pores should be large enough to allow an access of the target macromolecules. Large molecules can be trapped in the small pores which become clogged. This may result in less efficient separation and lower purification yield. In addition, pressure on chromatographic support might increase significantly and this can cause a physical damage of the support. The choice of the support with a particular pore size should be made carefullysince the binding capacity can be reduced too, due to the reduction of surface area. The subject of my doctoral thesis was to find an appropriate way to functionalize the monolith in order to obtain high binding capacity forbiomolecules at the lowest possible pressure drop. One of the frequently used techniques is the introduction of polymer chains (tentacles) by grafting. The results of this study demonstrate that the grafted monoliths exhibit at least two to three fold higher dynamic binding capacity over a broad range of molecular sizes (including pDNA) than the non-grafted analogues. Although the introduction of polymer chains onto the surface of methacrylate monoliths led to a decrease of permeability, their capacity is still significantly higher then those of the non-grafted monoliths having the same permeability. Since the flow-unaffected properties were preserved, grafted methacrylate monoliths may become a resin of choice for downstream processing of various macromolecules. Further improvement of the purification process of biomolecules can be made for productivity, selectivity and simpler handling. Ideally, single chromatographic medium would have all three characteristics, which would allow purification in a single chromatographic step. By the grafting of linear hydrophobic chains and the subsequent functionalization of the remaining epoxy groups to the anion groups, we managed to prepare a monolith with mixed adsorption properties, which has proved effective in the pDNA purification process.
Keywords: anion-exchange chromatographie; anionsko izmenjavalni kromatografski nosilci; CIM monoliths; CIM monoliti; DEAE; dinamična vezna kapaciteta; Disertacije; dynamic binding capacity; functionalization; funkcionalizacija; grafting; graftiranje; kombinirani monoliti; Kromatografski nosilci; mixed-mode monoliths; padec tlaka; permeability; prepustnost; pressure drop; proteini; proteins